1983
DOI: 10.1093/nar/11.19.6723
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence ofmetF, theE. colistructural gene for 5–10 methylene tetrahydrofolate reductase and of its control region

Abstract: The nucleotide sequence of the E.coli metF gene (888 nucleotides), coding for 5-10 methylene tetrahydrofolate reductase, has been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…The function of the C-terminal domain of plant MTHFRs, which are insensitive to AdoMet, is unknown (9). The NADH-dependent, AdoMet-insensitive MTHFR of Escherichia coli (MetF) lacks the C-terminal domain (15)(16)(17).…”
mentioning
confidence: 99%
“…The function of the C-terminal domain of plant MTHFRs, which are insensitive to AdoMet, is unknown (9). The NADH-dependent, AdoMet-insensitive MTHFR of Escherichia coli (MetF) lacks the C-terminal domain (15)(16)(17).…”
mentioning
confidence: 99%
“…We decided in 1981 to study the structure and regulation of the enzymes leading to methionine from homoserine, and with Mario Zakin, Claude Parsot, Nathalie Duchange, Isabelle Saint Girons, and Alice Dautry, we determined the primary structure of aspartokinase II-homoserine dehydrogenase II, cystathionine-γ -synthase, β-cystathionase, and methylene tetrahydrofolate reductase, as well as that of the methionine repressor we had mentioned in our 1953 paper (28,47,48,56). All of the methionine genes, with the exception of metH and metG, are subject to repression by methionine and the repression is mediated through the MetJ gene product, a common aporepressor.…”
Section: Back To the Institut Pasteur (1969-1989): The Sequence Of Thmentioning
confidence: 99%
“…It was reasonable to assume that the repressor binding sites should be similar for all genes regulated via repression by methionine. Preliminary studies had shown us that upstream two of the structural genes, homologous sequences could be operator structures recognized by the same regulatory protein (48). Further work showed us that the repressor binding site is composed of an 8-nucleotide-long unit (3).…”
Section: Back To the Institut Pasteur (1969-1989): The Sequence Of Thmentioning
confidence: 99%
“…The pertinent DNA sequences of the metA, metC, metF, and metJ/metBL promoter regions contain from two to five imperfect, tandem repeats of the Met-box consensus sequence (3,4,7,18,24,25). The homology of individual Met-box sequences varies significantly within and between met regulon elements (3, 4).…”
mentioning
confidence: 99%